Optimization of the Fabrication of Sustainable Ceramsite Adsorbent from Coal Fly Ash/Waterworks Sludge/Waste Glass for Decolorization of Malachite Green - Weicheng Fang; Xingxing Cheng; Chang-Jung Sun; Hongfei Xiao; Jing Wang (Adsorption Science & Technology)
As a traditional dye, malachite green (MG) poses a threat to our environment and health. To decolorize MG, a composite ceramsite adsorbent composed of coal fly ash (CFA), sewage treatment sludge (STS), and waste glass (WG) with a quality ratio of 3 : 3 : 4, respectively, was prepared. The optimal preparation parameters were determined as follows: preheating temperature=600°C, sintering temperature=1157°C, and sintering time=17 min. Under optimal conditions, scanning electron microscopy (SEM) images show that the X-Com-ceramsite sample exhibits rough features and a porous structure. The obtained X-Com-ceramsite has a good MG decolorization effect (92% decolorization rate with an initial MG concentration of 56.876 mg/L). The qmax value of MG can reach up to 37.6 mg/g. The retention degree of MG in the X-Com-ceramsite with a relatively higher pH is stronger, and the adsorption process is spontaneous and endothermic. Synchronous fluorescence, two-dimensional correlation spectroscopy (2D-COS), and Fourier transform infrared spectroscopy (FT-IR) proved that the sensitivity of the C-O/C-O-O functional groups of the carbohydrates on the surface of the X-Com-ceramsite has a higher binding affinity toward MG as the initial concentration of MG changes.